PENGARUH DISIPLIN KERJA, ETIKA KERJA, DAN PROFESIONALISME KERJA TERHADAP KINERJA PEGAWAI (STUDI PADA PEGAWAI PT XYZ) - Muh Rangga Ariansyah; Wasi Bagasworo; Ossi Ferli; Meta Andriani (Ibs Press, 2025)
Every company must establish a work culture that is disciplined, ethical, and professional to improve both individual and organizational performance. This study aims to examine “The Influence of Work Discipline, Work Ethics, and Work Professionalism on Employee Performance (A Case Study on Employees of PT XYZ).” The independent variables in this study are Work Discipline, Work Ethics, and Work Professionalism, while the dependent variable is Employee Performance. Hypothesis testing in this study was conducted using the Partial Least Square (PLS) method with SmartPLS 4.0 software. Data collection was carried out through questionnaires distributed to respondents in printed form. The sample consisted of 40 employees of PT XYZ. The results of the analysis show that Work Discipline has a positive and significant effect on Employee Performance, while Work Ethics and Work Professionalism do not have a positive and significant effect on Employee Performance.